Deficiency of Boron and Molybdenum in Soils and Crops of India and their Amelioration - Behera, S. K.; Shukla, A. K.; Lakaria, B. L (Indian Farming, 2015)
Due to adoption of intensive cropping practices, nature of parent materials and soil processes affected by various climatic conditions, deficiency of B and Mo in soils of India has been recorded. Since these nutrients play important role in plant growth and development, there is urgent need to correct this deficiency in soil in order to obtain higher crop yields. B and Mo deficiency in soil can be corrected by suitable application of B and Mo containing fertilizers available in the market. The amount, mode and frequency of application need to be decided depending upon the soil, crop and climatic conditions.